Association of Hypertension and Smoking with Ischaemic Stroke (Bangladesh Journal of Medical Biochemistry, 2013)
Hypertension is one of the most important modifiable risk factors for ischemic stroke. Cigarette smoking is a risk factor for atherosclerotic disease. There is a strong relationship between hypertension and cigarette smoking with ischaemic stroke. A case control study was undertaken to see the association of hypertension and cigarette smoking with ischaemic stroke. The study was done from January to December 2009 in the Department of Biochemistry, Dhaka Medical College, Dhaka. A total of 60 subjects were selected as study population. Among them 30 were diagnosed case of ischaemic stroke and 30 were age-and sex-matched control subjects. It was found that 60% patients of case group and 20% respondents of control group were hypertensive and diffrence was significant. Study showed that 56.66% of cases and 53.33% of controls were smoker and the findings were insignificant. The mean duration of smoking was 27.41 ± 2.98 years in cases and 15.63 ± 2.85 years in controls which was significant. The study suggests that hypertension is significantly associated with ischaemic stroke and longer duration of smoking also associated with ischaemic stroke. DOI: http://dx.doi.org/10.3329/bjmb.v3i1.13802 Bangladesh J Med Biochem 2010; 3(1): 16-18